A portable system for economical nucleic acid amplification testing - Dong, Hui; Mo, Jin; Yu, Yongjian; Xie, Wantao; Zheng, Jianping; Jia, Chao (Frontiers in Bioengineering and Biotechnology, 2023)
Regular and frequent large-scale screening, along with rapid detection of pathogens, provides a reliable solution for controlling pandemics such as Coronavirus Disease 2019 . In this study, we have developed a digital point-of-care testing (POCT) system using microfluidic paperbased analytical devices (μPADs) that includes temperature tuning and fluorescent detection components. We have also developed fluorescent image acquisition and self-recognition programs to improve the intelligent and autonomous level of operation. Based on nucleic acid amplification test (NAAT) which is a typical molecular biology techniques for detecting and amplifying nucleic acids, such as DNA or RNA, we have successfully detected artificially synthesized SARS-CoV-2 gene fragments (ORF1ab gene, N gene, and E gene) with total reagent consumption of only 2.2μL per readout, which is a mere 11% of the requirements of conventional in-tube methods. The power dissipation of the system was low to 6.4 W. Our testing results demonstrated that the approach had a limit of detection of 1000 copies/mL, which was equivalent to 1 copy or single RNA template per reaction. Based on standard curve analysis, the quantity of the target templates can be determined.